2015
DOI: 10.1128/ec.00094-15
|View full text |Cite
|
Sign up to set email alerts
|

A MORN Repeat Protein Facilitates Protein Entry into the Flagellar Pocket of Trypanosoma brucei

Abstract: The parasite Trypanosoma brucei lives in the bloodstream of infected mammalian hosts, fully exposed to the adaptive immune system. It relies on a very high rate of endocytosis to clear bound antibodies from its cell surface. All endo-and exocytosis occurs at a single site on its plasma membrane, an intracellular invagination termed the flagellar pocket. Coiled around the neck of the flagellar pocket is a multiprotein complex containing the repeat motif protein T. brucei MORN1 (TbMORN1). In this study, the phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 53 publications
(90 reference statements)
7
51
0
Order By: Relevance
“…In this way, the contribution of other sequences or domains could be discounted. The MORN1 protein from the early-branching eukaryote Trypanosoma brucei is an ideal candidate in this regard, and has the advantage of also being well-characterised at a cell biology level (Morriswood, He et al, 2009, Esson, Morriswood et al, 2012, Morriswood, Havlicek et al, 2013, Morriswood & Schmidt, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, the contribution of other sequences or domains could be discounted. The MORN1 protein from the early-branching eukaryote Trypanosoma brucei is an ideal candidate in this regard, and has the advantage of also being well-characterised at a cell biology level (Morriswood, He et al, 2009, Esson, Morriswood et al, 2012, Morriswood, Havlicek et al, 2013, Morriswood & Schmidt, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In functional terms, depletion of TbMORN1 by RNAi in the mammalian-infective form of the parasite resulted in a lethal phenotype (Morriswood et al, 2009). Functional analysis indicated that the protein might be involved in endocytosis, as well as regulating the flow of macromolecular cargo through the neck of the flagellar pocket (Morriswood & Schmidt, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Cytoskeleton- and flagella-enriched fractions were prepared following a published protocol5960 with minor modifications. Briefly, 1×10 8 cells were harvested by centrifugation (1500 × g, 10 min, 4 °C) and washed in 1 ml PEME buffer (2 mM EGTA, 1 mM MgSO4, 0.1 mM EDTA, 0.1 M piperazine-N,N′-bis (2-ethanesulfonic acid)-NaOH (PIPES-NaOH), pH 6.9).…”
Section: Methodsmentioning
confidence: 99%
“…The bilobe is located near the Golgi apparatus; it is thought to function in Golgi apparatus replication and as an adaptor during cytokinesis [34]. Recently, TbMORN1 depletion experiments suggested that this protein allows access of endocytic tracers into the flagellar pocket [35].…”
Section: Microtubulesmentioning
confidence: 99%